2010
DOI: 10.1016/j.micres.2009.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic karyotyping and construction of a bacterial artificial chromosome library of the winter mushroom Flammulina velutipes

Abstract: An electrophoretic karyotype of Korean Flammulina velutipes was obtained using contour-clamped homogeneous electric field (CHEF) gel electrophoresis. The monokaryotic progenies (4019-20 and 4019-18) and a dikaryotic strain (4019-2018) had 6-8 chromosomes, with sizes ranging from 1.6 to 5.8 megabase (Mb) pairs. Among the 3 strains that were examined, strain 4019-20 resolved into at least 7 chromosomes, with a total genome size of approximately 26.7Mb. We selected several chromosome-specific genes from the cDNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
0
11
1
Order By: Relevance
“…The important point is that β-mercaptoethanol did not influence DNA purity and length. Only a few reports have described the use of β-mercaptoethanol for BAC library construction [15][16][17][18], and thus β-mercaptoethanol is uncommon chemical regent for large-insert library construction. The reason for use has not been described at all, and the usage, efficiency and side effects of β-mercaptoethanol have never been assessed in detail.…”
Section: Resultsmentioning
confidence: 99%
“…The important point is that β-mercaptoethanol did not influence DNA purity and length. Only a few reports have described the use of β-mercaptoethanol for BAC library construction [15][16][17][18], and thus β-mercaptoethanol is uncommon chemical regent for large-insert library construction. The reason for use has not been described at all, and the usage, efficiency and side effects of β-mercaptoethanol have never been assessed in detail.…”
Section: Resultsmentioning
confidence: 99%
“…By this method, electrophoretic karyotypes have been revealed for many fungi including cultivated edible mushrooms such as A. bisporus (Royer et al 1991(Royer et al , 1992Sonnenberg et al 1991;Lodder et al 1993), L. edodes (Arima and Morinaga 1993), Pleurotus species (Sagawa and Nagata 1992;Tamai et al 1995), and F. velutipes (Kim et al 2000;Tanesaka et al 2003;Park et al 2010). Various reports have suggested that F. velutipes has at least six (Kim et al 2000), or six or seven (Park et al 2010), or seven or eight (Tanesaka et al 2003) haploid chromosomes. Chromosome-specific probes have also been constructed by assignment of DNA probes prepared from a cDNA library to CHEF-separated chromosomes (Kim et al 2000;Park et al 2010).…”
mentioning
confidence: 99%
“…Various reports have suggested that F. velutipes has at least six (Kim et al 2000), or six or seven (Park et al 2010), or seven or eight (Tanesaka et al 2003) haploid chromosomes. Chromosome-specific probes have also been constructed by assignment of DNA probes prepared from a cDNA library to CHEF-separated chromosomes (Kim et al 2000;Park et al 2010). On the other hand, assignment using DNA probes prepared from a genetic linkage map is more effective to elucidate the karyotype involved in haploid chromosome number and genome size and for analysis of meiotic behavior, as demonstrated in A. bisporus (Royer et al 1991(Royer et al , 1992Kerrigan et al 1993;Sonnenberg et al 1996).…”
mentioning
confidence: 99%
See 2 more Smart Citations